2017
DOI: 10.1097/md.0000000000009007
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spinal epidural hematoma mimicking transient ischemic attack

Abstract: Rationale:Spontaneous spinal epidural hematoma (SSEH) is a rare but highly disabling neurological emergency. The initial presentations are variable. Most patients of SSEH present with paraplegia or tetraplegia clinically, but recurrent hemiparesis with complete spontaneous recovery, mimicking transient ischemic attack (TIA), is a very rare initial presentation of SSEH.Patient concerns:A 71-year-old female presented to the emergency department with 2 episodes of transient right hemiparesis in 5 hours. Two days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
18
1
Order By: Relevance
“…In the case series by Liao et al, 54% of patients reported a straining-associated event during the initial attack, supporting the venous theory [1]. This is especially true in the older patients [2]. They have slow progression of neurological deficits.…”
Section: Review Of Literaturementioning
confidence: 83%
See 3 more Smart Citations
“…In the case series by Liao et al, 54% of patients reported a straining-associated event during the initial attack, supporting the venous theory [1]. This is especially true in the older patients [2]. They have slow progression of neurological deficits.…”
Section: Review Of Literaturementioning
confidence: 83%
“…The venous theory will not be applicable in the cervical region [1,2]. The venous pressure is lower than the intrathecal pressure [1,2]. Secondly, the cervical epidural hematoma usually produces rapid deterioration.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…However, if misdiagnosed as TIA and antiplatelet therapy is initiated, cervical epidural hematoma could deteriorate, which might require emergency decompressive laminectomy and result in permanent sequela or death. 4,5 Therefore, spontaneous cervical epidural hematoma should always be considered as an important differential diagnosis in patients with neck pain and transient hemiparesis mimicking TIA. In patients with transient hemiparesis mimicking TIA, neurological examination is not helpful because of improvement of neurological abnormalities.…”
mentioning
confidence: 99%